2010
DOI: 10.1590/s1413-86702010000200002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of family and neighbors of an individual infected with Wuchereria bancrofti from a non-endemic area in the city of Maceió, Brazil

Abstract: This study received fi nancial support from PPSUS MS/CNPq/FAPEAL, PAHO/WHO. ABSTRACTThe family and neighbors of a patient infected with W. bancrofti microfi lariae were assessed aiming to evaluate the occurrence of cases of lymphatic fi lariasis in a non-endemic area in the city of Maceió, in the Brazilian state of Alagoas. The patient had previously lived in an endemic focus; however, he has been living in an area where the parasite has never been detected for the past ten years. Female ingurgitated Culex qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Different studies have reached independent conclusions regarding the possible risk. One study from Brazil found that one antigen-positive individual did not seem to pose a significant risk for transmission, as no one in the vicinity had become infected in the 10 years he lived in this non-endemic community [11] . However, this study was only observational and based on a single individual and therefore may not be generalizable to the overall population.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have reached independent conclusions regarding the possible risk. One study from Brazil found that one antigen-positive individual did not seem to pose a significant risk for transmission, as no one in the vicinity had become infected in the 10 years he lived in this non-endemic community [11] . However, this study was only observational and based on a single individual and therefore may not be generalizable to the overall population.…”
Section: Discussionmentioning
confidence: 99%